Pine Flower Waste Innovation As A Plant Based Program Augmented Reality - Ayik Bela Saputra; Imam Muhtarom; Ni’matul Rochmaniyah; Ardhana Iswari Citra Padmi; Ika Rahmawati (Universitas Negeri Malang, 2018)
Indonesia one of the tropical countries in the world can not be separated from environment problems like other developing countries. One of the causes of declining environment quality is the decline of forests in Indonesia. In 2009, Indonesia’s forest area was by more than half, to about 88 million hectares. By the year 2013 the number is about 82 million hectares. One of the efforts to promote environment education is to familiarize planting plants to children from an early age from the school environment to the family environment. Therefore it is necessary an alternative in the form of planting media that can be used as a trigger tool of environmental care attitude and can feel the sensation of planting that educative by utilizing pine flower waste as an attractive and environmentally friendly planting medium. Besides as a planting medium is also intended as a instructional media especially elementary school students to high school students. This is because the planting medium has a goal to give an educative impression through information on plant species being planted and to increase awareness of the surrounding environment. If used as a medium of learning this planting media will bring up information about the plant being planted by way of scanning pot characters with gadgets then information about the classification of plants, root shapes, stems, leaves, flowers, how